Maternal Nutritional Status Governs Fetal Development by Modulating Imprinting Gene GAB1 ‐Mediated Trophoblast Differentiation in the Placenta - Fan, Mingming; Wu, Hongyu; Xie, Yuan; Liu, Ming; Yu, Xin; Wang, Feiyang; Xiao, Zhenyu; Wang, Hongmei; Shao, Xuan; Wang, Yan‐Ling (Cell proliferation, 2025)
The appropriate allocation of nutrients between the mother and the fetus during mammalian pregnancy primarily depends on a healthy placenta. Fetal growth restriction (FGR) is frequently associated with inadequate maternal nutrition supply and impaired placental function. The precise mechanisms linking maternal nutrient deficiency to compromised fetal and placental development remain largely elusive. In this study, we conducted an in‐depth analysis by integrating single‐cell/single‐nucleus RNA sequencing data from human and mouse placentas along with transcriptomic data from FGR placenta, identifying the GAB1 (GRB2‐associated binding protein 1) gene as a potential mediator of dysregulated maternal–fetal exchange, thereby affecting fetal growth. Using a mouse model, we demonstrated that food restriction significantly impeded fetal growth and disrupted placental labyrinth development. Through an in vitro trophoblast differentiation model, we revealed that nutritional restriction impaired GAB1 stability via LC3‐interacting region (LIR) motif‐mediated selective autophagic degradation, thereby hindering GAB1‐MAPK signalling‐enhanced trophoblast syncytialisation. These findings elucidate the mechanisms by which placental GAB1 links maternal nutrition status with fetal growth and suggest potential therapeutic strategies for managing pregnancy complications such as FGR.